Does Fentanyl Lead to Opioid-induced Hyperalgesia in Healthy Volunteers?: A Double-blind, Randomized, Crossover Trial. (February 2016) - Mauermann, Eckhard; Filitz, Joerg; Dolder, Patrick; Rentsch, Katharina M.; Bandschapp, Oliver; Ruppen, Wilhelm
Abstract : Background: Although opioids in general and remifentanil in particular have been shown to induce hyperalgesia, data regarding fentanyl are scarce. Thus, the authors investigated the effect of fentanyl dosing on pain perception and central sensitization in healthy volunteers using established pain models. Methods: Twenty-one healthy, male volunteers were included in this randomized, double-blind, crossover study and received either intravenous low-dose (1 μg/kg) or high-dose (10 μg/kg) fentanyl. Pain intensities and hyperalgesia were assessed by intracutaneous electrical stimulation, and cold pressor pain was used as an additional measure of acute pain. The primary outcome was hyperalgesia from 4.5 to 6.5 h after fentanyl administration. Results: A higher dose of fentanyl led to significantly decreased pain scores as measured by the numeric rating scale (0.83 units lower [95% CI, 0.63 to 1.02]; P < 0.001) but increased areas of hyperalgesia (+30.5% [95% CI, 16.6 to 44.4%]; P < 0.001) from 4.5 to 6.5 h after fentanyl administration. Allodynia did not differ between groups (+4.0% [95% CI, −15.4 to 23.5%]; P = 0.682).The high dose also led to both increased cold pressor pain threshold (+43.0% [95% CI, 29.7 to 56.3%]; P < 0.001) and tolerance (+32.5% [95% CI, 21.7 to 43.4%]; P < 0.001) at 4.5 to 6.5h. In the high-dose group, 19 volunteers (90%) required reminders to breathe, 8 (38%) required supplemental oxygen, and 12 (57%) experienced nausea. Conclusions: A higher dose of fentanyl increased hyperalgesia from 4.5 to 6.5 h in healthy volunteers while simultaneously decreasing pain scores. Abstract : High-dose (10 μg/kg) fentanyl infusion can increase cold pressor test pain threshold and tolerance 4.5 to 6.5 h after infusion. Simultaneously, high-dose fentanyl infusion can increase the area of hyperalgesia caused by electrical burn.Supplemental Digital Content is available in the text.